Charles Robert Maturin and the haunting of Irish romantic fiction - Morin, Christina (Manchester Gothic (Manchester, England)., 2017)
A clear, theoretically-grounded, chronological study of Maturin's six novels. A new critical paradigm by which to view and read Irish Romantic fiction. Offers the most comprehensive and up-to-date analysis of Maturin and his fiction available today.